THE LOCAL POLITICS OF ORTHODOXY: The Majelis Ulama Indonesia in the Post-New Order Banten (JOURNAL OF INDONESIAN ISLAM, 2012)
The Majelis Ulama Indonesia (MUI) has played an important role in guarding the Sunni orthodoxy in contemporary Indonesia. As it has chapters in almost parts of Indonesia in the provincial, district and municipality level, this role has been also translated into the local context. The strength of the MUI stems from “semi-officiality” and “semi-representative” nature of the organisation. This article is aimed to analyse this role in the post-New Order period, after the establishment of the Majelis Ulama Indonesia (MUI) of Banten province in 2001, especially in dealing with deviant beliefs or sects and shirk (polytheist) and bid‘ah (religious innovation) practices. It is to show that orthodoxy and heterodoxy is not purely religious, but also political, as this is related to the problem of authority and power.